A mighty heart the brave life and death of my husband Danny Pearl - Pearl, Mariane; Crichton, Sarah (New York : Simon & Schuster Audio, 2003)
Marianne Pearl, wife of the Wall Street Journal reporter who was kidnapped and murdered by Islamic terrorists in Pakistan, tells the story of his life and death.
Compact discs.
Read by the author.
Keywords: Pearl, Daniel, -- 1963-2002.; Pearl, Daniel, -- 1963-2002 -- Assassination; Journalists -- United States -- Biography; Journalists -- Crimes against -- United States